Molecular survey of Cytauxzoon spp. and Hepatozoon spp. in felids using a novel real-time PCR approach - Grillini, Marika; Beraldo, Paola; Frangipane di Regalbono, Antonio; Dotto, Giorgia; Tessarin, Cinzia; Franzo, Giovanni; Marchiori, Erica; Modrý, David; Simonato, Giulia (Frontiers in Veterinary Science, 2023)
Tick-transmitted apicomplexans of the genera Cytauxzoon and Hepatozoon affect a wide range of felids worldwide, but little is known about them. Recently, several studies addressed the species circulating in Europe, their distribution, and their hosts. Molecular assays are the method of choice for their detection. Unfortunately, conventional PCRs already described are time- and cost-consuming and specific for either Hepatozoon or Cytauxzoon detection. This study was developed to evaluate (i) the occurrence of Cytauxzoon and Hepatozoon in felids using a fast and cost-saving real-time PCR capable of detecting both protozoa simultaneously, (ii) the distribution of Cytauxzoon and Hepatozoon species in north-eastern Italy, and (iii) the involvement of other susceptible felid hosts in the same area. An SYBR® Green-based real-time PCR with primers targeting the 18S-rRNA was validated and applied to 237 felid samples, i.e., whole blood from 206 domestic cats and 12 captive exotic felids, and tissues from 19 wildcats. Positive results were obtained by melting temperature curve analysis due to the specific melting peak (i.e., 81°C Cytauxzoon spp.; 78–78.5°C Hepatozoon spp.). Positive samples were subjected to conventional PCR, followed by sequencing for species identification. Phylogenetic analyses were performed to assess relatedness among European isolates. Data on domestic cats (age class, sex, origin, management, and lifestyle) were recorded, and statistical analyses were performed to identify potential risk factors. A total of 31 (15%) domestic cats were positive for Hepatozoon spp. (i.e., 12 for H. felis, 19 for H. silvestris), while six (2.9%) for C. europaeus. The prevalence of Hepatozoon felis was significantly (p < 0.05) higher in domestic cats, while H. silvestris was higher in strays and animals from the Eastern region (i.e., Friuli-Venezia Giulia). Cytauxzoon europaeus was detected only in stray cats from Friuli-Venezia Giulia (province of Trieste). Among captive felids, one tiger was infected with H. felis and another with H. silvestris; eight out of 19 (42%) wildcats were positive for Hepatozoon spp. (i.e., six with H. felis, two with H. silvestris) and four out of 19 (21%) for Cytauxzoon europaeus. Outdoor lifestyle and origin (i.e., Friuli-Venezia Giulia region) were the most relevant risk factors for H. silvestris and C. europeus infections. Conversely, H. felis was most frequently isolated from domestic cats, suggesting different modes of transmission.